Adsorption of polyacrilic acid onto aluminium oxide and silicon carbide = Adsorpcija poliakrilne kiseline na aluminijevu oksidu i silicijevu karbidu : Doctoral Disertation - Marković, Berislav, kemičar (B. Marković, 1996)
Polymer adsorption at solid/liquid interface is influenced by various polymer, substrate and solution properties. In order to obtain a full insight into the kinetics and equilibrium of polymer adsorption process, a thorough investigation of these properties is needed. For this study, three different alumina samples were chosen as substrate. Adsorption of polyacrilic acide was investigated also on silicon carbide platelets. The characterization of powder materials used has shown: - Scanning Electron Microscopy observation have revealed the hard, highly porous agglomerates of Linde A and Aldrich aluminas. Sumitomo AKP50 alumina sample consists of isolated, nonporous particles of uniform size. Silicon carbide platelets are very smooth with wide size distribution.